'I did try and point out about his dignity': a qualitative narrative study of patients and carers' experiences and expectations of junior doctors. Issue 1 (21st January 2018) - Kostov, Camille E; Rees, Charlotte E; Gormley, Gerard J; Monrouxe, Lynn V
Abstract : Objectives: For many years, the voice of patients has been understood as a critical element for the improvement of care quality in healthcare settings. How well medical graduates are prepared for clinical practice is an important question, but one that has rarely been considered from patient and public perspectives. We aimed to fill this gap by exploring patients and carers' experiences and expectations of junior doctors. Design: This comprises part of a wider study on UK medical graduates' preparedness for practice. A qualitative narrative methodology was used, comprising four individual and six group interviews. Participants: 25 patients and carers from three UK countries. Analysis: Data were transcribed, anonymised and analysed using framework analysis. Main results: We identified three themes pertinent to answering our research question: (1) sources of knowledge (sources of information contributing to patients and carers' perceptions of junior doctors' impacting on expectations); (2) desires for student/trainee learning (experiences and expectations of medical training); and (3) future doctors (experiences and expectations of junior doctors). We also highlight metaphorical talk and humour, where relevant, in the quotes presented to give deeper insights into participants' perspectives of the issues. Participants focused on personal and interpersonal aspects of being a doctor, such as respect and communication. There was a strong assertion that medical graduates needed to gain direct experience with a diverse range of patients to encourage individualised care. Participants narrated their experiences of having symptoms ignored and attributed to an existing diagnosis ('diagnostic overshadowing') and problems relating to confidentiality. Conclusions: Our findings support the view that patients and carers have clear expectations about junior doctors, and that patient views are important for preparing junior doctors for practice. There is a necessity for greater dialogue between patients, doctors and educators to clarify expectations and confidentiality issues around patient care.